Paradigma Ekonomi Syariah Dalam Faham Hegemoni Kapitalisme dan Sosialisme Sebuah Solusi Pola Hidup Muslim - Ika Prastyaningsih; Mohammad Ghozali; Andi Triyawan (Islamic Economics Journal, 2017)
Western countries with the economic system of capitalism have hegemonize all aspects of the economy of society, so that they dominate all countries in the world including Islam. The hegemony according to five things, that are:Defence, economic, socio-cultural, political, religion. The actualization and contextualization of the Islamic economic system is a form of criticism, and it will becomes a solution to the theory and economic system built on unhumanity (not egalitarian), especially capitalism and socialism. So that A Moslem must take Islam as a living system that regulates all sides of human life, which promises the welfare and falah.Because human life does not stop only in the world and it will be held accountable later in the world. The concept of Islamic Economics is not a collection of the good that exists in the capitalist and socialist economic system. But more than that though it looks the same but the value built on the Qur’an and Sunnah. The Kindness that exists in Islamic Economics has the greatness of value based on the revelation of Allah and Sirah Nabawiyah. The system of Islamic Economy can be accepted by all people in the world. Because it contains maslahah value for all creatures that exist on earth. The concept of justice built by Islam not only exist on the physical aspects but also the metaphysical. As well as welfare, not only in the realm of the body but also the Spiritual.